Analisis Yuridis terhadap Penjualan Harta Pailit yang Mudah Rusak di Bawah Nilai Likuidasi dalam Proses Kepailitan - Rafshahdy Azari Soediro (AHKAM, 2026)
The sale of bankruptcy assets is an important stage in the settlement of the bankruptcy estate to fulfill payments to creditors. In bankruptcy practice in Indonesia, the sale of perishable bankruptcy assets below liquidation value by the receiver raises legal issues concerning the validity of the receiver’s actions and the limits of their authority under Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUK PKPU). This study aims to analyze the regulation of the sale of perishable bankruptcy assets below liquidation value from the perspective of the UUK PKPU and to examine the validity of the receiver’s actions in such sales. This study used a normative juridical legal method with statutory and conceptual approaches. Legal materials were obtained through a literature study of laws and regulations, journals, and other relevant provisions, then analyzed descriptively and qualitatively. The results show that Article 107 of the UUK PKPU grants discretion to the receiver to sell perishable objects in order to prevent a decline in the value of bankruptcy assets. However, Article 185 paragraphs (1), (2), and (3) of the UUK PKPU still require that the sale of bankruptcy assets must first be conducted publicly through an auction mechanism. If the auction fails and is proven by auction minutes, a private sale may be conducted with the permission of the Supervisory Judge. Decree of the Chief Justice of the Supreme Court of the Republic of Indonesia Number 109/KMA/SK/IV/2020 also affirms that the private sale value must not be below the liquidation price. Thus, the sale of perishable bankruptcy assets below liquidation value can only be legally justified if there is an urgent condition that clearly threatens the loss of the economic value of the bankruptcy assets, is carried out in good faith, obtains permission from the Supervisory Judge, does not harm the bankruptcy estate, and is intended to protect the rights and interests of creditors. This study contributes to strengthening bankruptcy law studies, particularly concerning the limits of the receiver’s discretion in settling perishable bankruptcy assets.